Social issues and post-disaster recovery: A qualitative study in an Iranian context. (September 2015) - Alipour, Fardin; Khankeh, Hamidreza; Fekrazad, Husain; Kamali, Mohammad; Rafiey, Hassan; Ahmadi, Shokoufeh
The physical impacts of a disaster are usually the most obvious impacts, and they are easily measured. However, there is not sufficient in-depth understanding of social issues arising after disasters. This qualitative study explored three main concepts regarding social issues after an earthquake in an Iranian context: social vulnerability, social uncertainty and confusion, and ignorance of local social capital. Negligence of social issues after disasters leads to delays in returning back to normal life. Policymakers are encouraged to take a comprehensive plan into account which considers these issues and facilitates the process of returning to normal life after earthquakes.